Modelling students’ understanding of introductory statistical concepts: a cross sectional study using rasch measurement model and structural equation modelling / Nor Zatul-Iffa Ismail - Ismail, Nor Zatul-Iffa (Institute of Graduate Studies, UiTM, 2014)
Teaching and learning of statistics is becoming an increasingly important issue in statistical education. One pressing issue is how to continuously improve the teaching and learning of statistics at the tertiary level. Given its importance, statistical education researchers have attempted to investigate factors that relate to students’ learning outcomes in statistics. Among the continuous issues of concern is how to improve the teaching and learning of statistics at the tertiary level. Despite the great emphasis on the importance of statistics, students are still facing difficulty in learning statistics.